2014
DOI: 10.2514/1.a32449
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Analysis of Complex Spacecraft Using Systems-Theoretic Process Analysis

Abstract: A new hazard analysis technique, called System-Theoretic Process Analysis, is capable of identifying potential hazardous design flaws, including software and system design errors and unsafe interactions among multiple system components. Detailed procedures for performing the hazard analysis were developed and the feasibility and utility of using it on complex systems was demonstrated by applying it to the Japanese Aerospace Exploration Agency H-II Transfer Vehicle. In a comparison of the results of this new ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 4 publications
0
45
0
Order By: Relevance
“…From the 13 common identified hazards, it can be observed that both methods found software error type hazards covering the dynamic behavior of the system. In Ishimatsu et al (2014); Thomas and Leveson (2011); Leveson et al (2012); Nakao et al (2011);Fleming et al (2012Fleming et al ( , 2013, the authors have mentioned that the traditional analysis methods (FMEA, FTA, etc.) cannot identify software errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 13 common identified hazards, it can be observed that both methods found software error type hazards covering the dynamic behavior of the system. In Ishimatsu et al (2014); Thomas and Leveson (2011); Leveson et al (2012); Nakao et al (2011);Fleming et al (2012Fleming et al ( , 2013, the authors have mentioned that the traditional analysis methods (FMEA, FTA, etc.) cannot identify software errors.…”
Section: Discussionmentioning
confidence: 99%
“…The authors presented the advantages and disadvantages of these methods and concluded their study with an attempt of combining both deductive (top-down) and inductive (bottom-up) risk/safety analysis methods. Ishimatsu et al (2014) compared the STPA hazards analysis results with the FTA analysis results that were used to certify the H-II Transfer Vehicle (HTV). The HTV is an unmanned cargo transfer spacecraft that is launched from the Tanegashima Space Center aboard the H-IIB rocket and delivers supplies to the international space station (ISS).…”
Section: Related Workmentioning
confidence: 99%
“…In [10][11][12] the fact is also confirmed, that the causes of many incidents and accidents through software are in the software requirements specification (SRS), rather than in coding. Today the evaluation of measures for the software quality subcharacteristics and characteristics, and indicators for the software quality metrics is conducted only for the ready source code [12].…”
Section: Introductionmentioning
confidence: 86%
“…Analysis of the impact of software quality on the work of complex hardware and software systems [10][11][12] showed the important trend (that should be considered when evaluating and ensuring the software quality): software quality evaluation at the design stage will provide the opportunity for early detection of errors, for improving the software quality and for reducing the costs in its development. In [10][11][12] the fact is also confirmed, that the causes of many incidents and accidents through software are in the software requirements specification (SRS), rather than in coding.…”
Section: Introductionmentioning
confidence: 99%
“…The original FMEA method, best suited to the failure of single component was extended to other entities like computer based control systems or event human procedures (Ishimatsu et al, 2010). The authors do not overlook these progresses but think they do not change significantly the landscape as far as identifying emerging risks is concerned.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%